Kajian Akidah dan Metologi Dakwah Kumpulan AL-AHBASY - Muhammad Yusuf Khalid; Syamsul Bahri Andi Galigo; Ali Ya'kub Matondang (Universiti Sains Islam Malaysia, 2024)
This research aims to study closely the Theology and Da'wah methodology of association Al-Ahbasy. This reseach used library reseach by analyzing all written data available in Malaysia about this association, including information from the web site which belongs to the rival of this association. This research found that the Theology of this association is in line with the Theology of the school of Ahli Sunnah wal Jamaah, however, the methodology of da'wah used by this association is some times unwise such as using harsh words and attacking some muslim scholars without showing any respect to them. The out come of this research can be regarded as a guidline for those who have no background about this association, especially in the modern time where many muslim groups regarded as terrorists partly because of their deviated methodology of da'wah.